HEARTBEAT ALERTING SECURITY SYSTEM FOR WOMEN - Mohan, Aparna M; Mohan, Amal M; V R, Deepa V R; MG, Gireeshan (International Journal of Psychosocial Rehabilitation, 2020)
Safety of Women has become a major issue. The crime rates against women in the country have only risen to a great extent. Women think twice before stepping out of their homes, especially at the night. A new approach is given towards the security of women in the form of a device. The objective of the device is to provide women with a tool that can provide them security and ensure their safety in case of any mishap. The paper proposes a better approach to the GSM Technology which makes use of sudden monitoring of heart beat if any mishap happens the alert notification are send to the priority ones within few seconds. The heart beat module will reads the highest heartbeat rate and GSM/GPS module for alerting and location tracking.